Antibiotic resistance of Streptococcus pneumoniae colonising the nasopharynx of HIV‐exposed Tanzanian infants. Issue 11 (2nd September 2015) - Bles, P.; de Mast, Q.; van der Gaast‐de Jongh, C. E.; Kinabo, G. D.; Kibiki, G.; van de Ven, A.; de Jonge, M. I.
Abstract Objectives To determine antibiotic susceptibility of colonising pneumococcal serotypes in HIV‐exposed infants before the introduction of the 13‐valent pneumococcal conjugate vaccine (PCV13), because HIV‐exposed infants are at increased risk of invasive pneumococcal infections. Methods Antibiotic susceptibility of 104 pneumococcal isolates, cultured from the nasopharynx from Tanzanian HIV‐exposed infants, was determined using the disc diffusion method and the E‐test according to EUCAST version 4.0 (2014) criteria. Results A total of 69.2% of isolates were intermediately susceptible for benzyl penicillin (MIC 0.06–2 mg/l ); no high‐level resistance was found. All isolates but one were susceptible to ampicillin. Regarding non‐beta‐lactam antibiotics, 19.2% of isolates were resistant to doxycycline, 3.8% to erythromycin and 97.1% to trimethoprim/sulfamethoxazole. A total of 15.4% of isolates were resistant to three antibiotic classes or more. There were no differences in antibiotic susceptibility between vaccine and non‐vaccine serotypes. Reduced susceptibility of colonising pneumococcal isolates for commonly used antibiotics is common in HIV‐exposed Tanzanian infants. Conclusions High‐dose penicillin and ampicillin remain appropriate first choices for non‐meningeal pneumococcal infections in this group.